2013
DOI: 10.1111/jasp.12174
|View full text |Cite
|
Sign up to set email alerts
|

Achieving success at work: development and validation of the Motivational Climate at Work Questionnaire (MCWQ)

Abstract: Although work represents an important achievement setting, research on the perceived motivational climate, as defined by the achievement goal theory (AGT), remains limited. Calls have been made for research on the salience of such situational influences based on traditional AGT. Therefore, the aim of this research was to develop a scale to measure the motivational climate at work. In a pilot study, participants completed a developed questionnaire and the findings supported psychometric properties of the questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
200
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(214 citation statements)
references
References 105 publications
9
200
0
5
Order By: Relevance
“…In a performance motivational climate instructors encourage social comparison, superficially stimulate students during learning process using on regulative evaluation and recompensing performance results (Ames, 1992;Ames & Archer, 1988;Murcia, Camacho, & Rodríguez, 2008;Keegan, Spray, Harwood, & Lavallee, 2010), and enhance thereby the competition among students complimenting the most talented students (Cervelló & Santos-Rosa, 2001;Nicholls, 1989;). Performance-related motivational climate induces feelings of anxiety, stress, confusion, boredom and withdrawal, as it prevails lack of motivation (Liukkonen, Barkoukis, Watt, & Jaakkola, 2010;Braithwaite, Spray, & Warburton, 2011;Cumming, Smoll, Smith, & Grossbard, 2007;Nerstad, Roberts, & Richardsen, 2013;Van De Pol et al, 2012;Granero-Gallegos et al, 2014;Ommundsen & KvalØ, 2007). Research has identified further behaviors and interactions that contribute to motivational climate, such as the influence between peers, based on promoting cooperation, support, affection, competition, disagreement and friendships (Vazou, Ntoumanis, & Duda, 2005;Keegan, Spray, Harwood, & Lavallee, 2009;Keegan, Spray, Harwood, & Lavallee, 2010;Beltman & Volet, 2007;Bengoechea & Strean, 2007;Weiss, Amorose, & Wilko, 2009).…”
Section: Motivational Climatementioning
confidence: 99%
“…In a performance motivational climate instructors encourage social comparison, superficially stimulate students during learning process using on regulative evaluation and recompensing performance results (Ames, 1992;Ames & Archer, 1988;Murcia, Camacho, & Rodríguez, 2008;Keegan, Spray, Harwood, & Lavallee, 2010), and enhance thereby the competition among students complimenting the most talented students (Cervelló & Santos-Rosa, 2001;Nicholls, 1989;). Performance-related motivational climate induces feelings of anxiety, stress, confusion, boredom and withdrawal, as it prevails lack of motivation (Liukkonen, Barkoukis, Watt, & Jaakkola, 2010;Braithwaite, Spray, & Warburton, 2011;Cumming, Smoll, Smith, & Grossbard, 2007;Nerstad, Roberts, & Richardsen, 2013;Van De Pol et al, 2012;Granero-Gallegos et al, 2014;Ommundsen & KvalØ, 2007). Research has identified further behaviors and interactions that contribute to motivational climate, such as the influence between peers, based on promoting cooperation, support, affection, competition, disagreement and friendships (Vazou, Ntoumanis, & Duda, 2005;Keegan, Spray, Harwood, & Lavallee, 2009;Keegan, Spray, Harwood, & Lavallee, 2010;Beltman & Volet, 2007;Bengoechea & Strean, 2007;Weiss, Amorose, & Wilko, 2009).…”
Section: Motivational Climatementioning
confidence: 99%
“…However, experimental designs are the most effective in establishing causal relationships (Shadish, Cook, & Campbell, 2002), and experiments that, for example, manipulate the perceived motivational climate could be an interesting way to investigate this more closely. Bélanger et al (2013a;2013b) Third, the exclusive reliance on self-reported questionnaire data might cause concerns related to possible mono-method bias (Podsakoff, MacKenzie, Lee, & Podsakoff, 2003).…”
Section: Limitations and Research Directionsmentioning
confidence: 99%
“…A measure developed by Nerstad, Roberts, and Richardsen (2013b) was applied for measuring perceptions of the motivational climate (i.e., mastery and performance climate) at work. Participants were asked to give indications of how they perceived success to be defined in their work situations.…”
Section: Mastery Climatementioning
confidence: 99%
“…Menurut Nerstad, et al (2013), motivational climate dapat diterapkan di area pekerjaan karena karyawan juga dinilai berdasarkan ketercapaian unjuk kerja. Hal itu ditetapkan berdasar kriteria sukses dalam menghadapi tingginya beban pekerjaan dengan tuntutan psikologis serta intelektual.…”
Section: Yaitu Ego-involving (Performance Climate) Dan Task Involvingunclassified
“…Dimensidimensi tersebut membentuk work engagement menjadi keterlibatan individu dalam pekerjaan dengan menyenangkan, positif dan sarat akan semangat. Menurut Schaufeli, et al (2000), karyawan yang engaged dengan pekerjaannya akan selalu yakin pada kemampuan diri, dapat menarik hal positif dari umpan balik yang diterimanya, terkadang merasakan kelelahan dalam bekerja namun ia puas telah melakukan yang terbaik Nerstad, et al (2013) menyebutkan bahwa work engagement terkait erat dengan dimensi motivasi intrinsik, perasaan antusias, identifikasi dengan pekerjaan seseorang, tingkat aktivasi yang tinggi, dan pelaksanaan aktivitas yang bermakna bagi dirinya sendiri (Salanova, Agut, & Peiró, 2005;Salanova & Schaufeli, 2008). Dengan iklim kerja yang mengutamakan pengembangan kemampuan baru, improvement, pemahaman lebih baik akan pekerjaan dan dukungan untuk mengembangkan potensi masing-masing maka diprediksikan seseorang akan lebih attached, menikmati pekerjaannya.…”
Section: │ 63unclassified